Retinopathy among Adult Diabetics and Its Predictors in Northwest Ethiopia - Mulualem Birhan Takele; Dube Jara Boneya; Hailemariam Abiy Alemu; Tesfa Birlew Tsegaye; Molla Yigzaw Birhanu; Simegn Alemu; Tsige Gebre Anto (Journal of Diabetes Research)
Background. Diabetic retinopathy is the leading cause of blindness among working-aged adults worldwide, including developing countries such as Ethiopia, and the burden of diabetes-related blindness is undeniably posing a massive challenge to the health care system. Diabetes and its micro- and macrovascular complications are becoming more prevalent among Ethiopian diabetics. For that reason, the purpose of this study was to assess the incidence of diabetic retinopathy and its predictors among diabetics in Ethiopia. Methods. A hospital-based retrospective cohort study was conducted using 494 randomly selected diabetics aged above 18 years at Felege Hiwot Comprehensive Specialized Hospital from 2011 through 2014 and was followed until December 2019. The preliminary and longitudinal data was abstracted into demographics, clinical, and physiological attributes using a standardized structured questionnaire. The collected data was entered into the system using EpiData version 4.2 and analyzed using STATA version 14.0. The survival experience of the patients was assessed using the Kaplan-Meier survivor function. The predictors of diabetic retinopathy were identified by the Cox proportional hazard model. Bivariable and multivariable Cox proportional hazard models were computed, and variables having a P value of < 0.05 in the multivariable Cox proportional hazard model were declared as significant predictors of diabetic retinopathy. Results. During the follow-up, the overall incidence rate of diabetic retinopathy was 48 per 1000 person-years (95% CI: 40.0–57.0). Age in years (AHR 1.02; 95% CI: 1.00-1.04), fasting blood sugar level (AHR 1.02; 1.00-1.04), hypertension (AHR 2.61; 95% CI: 1.47-4.63), DM patients who had LDL>100 mg/dl (AHR 2.73; 95% CI: 1.32-5.64), total cholesterol>200 mg/dl (AHR 2.22; 95% CI: 1.08-4.55), and positive proteinuria (AHR 1.74; 95% CI: 1.10 -2.73) were found to be the significant predictors of diabetic retinopathy. Conclusion. The overall incidence rate of diabetic retinopathy was found to be high in both type 1 and type 2 DM. Age, fasting blood sugar levels, hypertension, proteinuria, dyslipidemia, and high systolic blood pressure were all predictors of the development of diabetic retinopathy. Controlling glycemia, dyslipidemia, proteinuria, and blood pressure is critical for halting the progression of diabetic retinopathy.